Hydrodynamic performance and surface characterisation of antifouling coatings after long-term marine exposure - E. Begovic; G. Assanelli; F. Aiello; A. Amico; A. Amoresano; G. Battaglia; C. Bertorello; L. Bonoldi; M. Bruscagin; F. De Luca; G. Fiori; C. Fontanarosa; et al. (Ocean Engineering, 2026)

How diet can affect the equivalence between production and concentration of short-chain fatty acids in the rumen of cattle - P.H.M. Rodrigues; F. Perna Junior; R.G.S. Nogueira; R.F. Carvalho; R.J. Tseu; A.J. Furtado; P.M. Meyer (Animal Feed Science and Technology, 2026)

Intake, digestibility and rumen fermentation in Nellore bulls grazing degraded or recovered pastures of Urochloa ssp. or the grass intercropped with pigeon pea - A.J. Furtado; A.L. Abdalla Filho; F. Perna Junior; R. Pasquini Neto; G.V. Silva; A.A.G. Lobo; L.M. Coelho; J.F. Bruno; A. Berndt; A.F. Pedroso; S.R. Medeiros; P.P.A. Oliveira; et al. (Animal Feed Science and Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Lithologies of Dimorphos revealed by boulder morphological classes - F. Tusberti; M. Pajola; L. Penasa; A. Lucchetti; M. Massironi; G. Munaretto; J. Beccarelli; R. Pozzobon; C. Rossi; G. Poggiali; N. Murdoch; C.Q. Robin; et al. (Icarus, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Opaque ventilated façades: Energy performance for different main walls and claddings - O. Roig; S. Summa; C. Pardal; A. Isalgue; C. Di Perna; F. Stazi (Energy and Buildings, 2024)

Thermal performance of a new low-cost ventilated load bearing masonry with wood-cement blocks - F. Stazi; S. Summa; O. Roig; G. Trozzi; C. Di Perna (Energy and Buildings, 2023)

Experimental and numerical study on a new thermal masonry block by comparison with traditional walls - S. Summa; G. Remia; C. Di Perna; F. Stazi (Energy and Buildings, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Impact of HIV infection on sustained virological response to treatment against hepatitis C virus with pegylated interferon plus ribavirin - P. Monje-Agudo; A. Castro-Iglesias; A. Rivero-Juárez; F. Martínez-Marcos; E. Ortega-González; L. M. Real; B. Pernas; N. Merchante; P. Cid; J. Macías; M. D. Merino; A. Rivero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Monitoring and modelling land surface dynamics in Bermejo River Basin, Argentina: time series analysis of MODIS NDVI data - V. Barraza; F. Grings; M. Salvia; P. Perna; A.E. Carbajo; H. Karszenbaum (International Journal of Remote Sensing, 2013)

p66Shc protein, oxidative stress, and cardiovascular complications of diabetes: the missing link - Pietro Francia; Francesco Cosentino; Marzia Schiavoni; Yale Huang; Enrico Perna; Giovani G. Camici; Thomas F. Lüscher; Massimo Volpe (Journal of Molecular Medicine, 2009)

Performance of two commercial blood IFN-γ release assays for the detection of Mycobacterium tuberculosis infection in patient candidates for anti-TNF-α treatment - M. Bocchino; A. Matarese; B. Bellofiore; P. Giacomelli; G. Santoro; N. Balato; F. Castiglione; R. Scarpa; F. Perna; G. Signoriello; D. Galati; A. Ponticiello; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Model investigation about the potential of C band SAR in herbaceous wetlands flood monitoring - F. M. Grings; P. Ferrazzoli; H. Karszenbaum; M. Salvia; P. Kandus; J. C. Jacobo‐Berlles; Pablo Perna (International Journal of Remote Sensing, 2008)

Prostaglandin E2 correlates with histamine production in human colorectal cancer - F. Cianchi; C. Cortesini; F. Perna; V. Fabbroni; C. Uliva; F. Fabrizi; L. Giannini; A. Vannacci; E. Masini (Inflammation Research, 2006)

Histamine and histidine decarboxylase up-regulation in colorectal cancer: correlation with tumor stage - E. Masini; V. Fabbroni; L. Giannini; A. Vannacci; L. Messerini; F. Perna; C. Cortesini; F. Cianchi (Inflammation Research, 2005)

Isotopic Model (NISOTOP) used to Investigate 15N-Urea Transformations in the Presence of Phenanthrene, Chrysene and Benzo(a)pyrene in a Soil–Plant System - S. Cervelli; F. Di Giovanni; C. Perna; D. Perret (Water, Air, & Soil Pollution, 2000)